Multi-criteria evaluation and multi-method analysis for appropriately selecting renewable energy sources in Colombia - Christian M. Moreno-Rocha; José R. Nuñez-Alvarez; Juan Rivera-Alvarado; Alfredo Ghisayz Ruiz; Enderson A. Buelvas-Sanchez (MethodsX)
This research explores the implementation of renewable energy technologies for power generation using multi-criteria decision-making (MCDM) methods, including AHP, FAHP, TOPSIS, and FUZZY-TOPSIS. Ten renewable energy alternatives were evaluated across seven geographic regions in Colombia, revealing variability in preferences depending on the method and scenario. Alternatives 6 and 4 frequently stood out, while others showed varied rankings. This study significantly contributes to the energy sector by offering a rigorous framework for selecting renewable generation technologies, supporting sustainable energy planning, and providing a model for replication in global contexts, some key points are: • The study applied systematic MCDM approaches to assess renewable energy sources. • Results demonstrated method-dependent variability and highlighted regional preferences. • It sets a benchmark for integrating sustainable practices into energy planning worldwide.